GENUS Gynoxys CASS (ASTERACEAE) IN THE DEPARTMENT OF AMAZONAS, PERU: DISTRIBUTION AND NEW RECORDS - CORONEL-CASTRO, Elver (2023)
In this study, we present the species of the genus Gynoxys recorded in the department of Amazonas, Peru. From March 2021 to October 2023, a review of exsiccata preserved in national herbaria, virtual databases of international herbaria, and field collections in different localities was carried out. We report 22 species of Gynoxys in Amazonas, of which two are new records for Peru and six are first reports for Amazonas. The genus is mainly distributed in the southern part of the department, inhabiting mainly moorlands and high altimontane forests of the Yungas, mostly located above 2900 meters above sea level (m a.s.l).